Health benefits and bioactive compounds of eggplant. (1st December 2018) - Gürbüz, Nergiz; Uluişik, Selman; Frary, Anne; Frary, Amy; Doğanlar, Sami
Highlights: Eggplant is a popular vegetable and an important dietary component in the developing world. Eggplant has numerous phytochemicals with beneficial nutritive effects. Increasing numbers of studies have revealed the pharmaceutical potential of eggplant. Abstract: Eggplant is a vegetable crop that is grown around the world and can provide significant nutritive benefits thanks to its abundance of vitamins, phenolics and antioxidants. In addition, eggplant has potential pharmaceutical uses that are just now becoming recognized. As compared to other crops in the Solanaceae, few studies have investigated eggplant's metabolic profile. Metabolomics and metabolic profiling are important platforms for assessing the chemical composition of plants and breeders are increasingly concerned about the nutritional and health benefits of crops. In this review, the historical background and classification of eggplant are shortly explained; then the beneficial phytochemicals, antioxidant activity and health effects of eggplant are discussed in detail.